ORGANIZATIONAL COMMITMENT MEDIATING WORK-FAMILY CONFLICT AND JOB SATISFACTION IN NURSING PERFORMANCE - Sarman, Rohmat; Kosim, Nanang; Sari, Ranti (Faculty of Economics and Business, University of Pasundan, 2023)
This study examines how nurses' performance is perceived regarding work-family conflict and job satisfaction and how organizational commitment plays a role in mediating this relationship at Pindad Bandung General Hospital. The research used a quantitative survey methodology with a sample of 66 female nurses. Data was collected through interviews, questionnaires, and observations, and path analysis was used to analyze the data. The results indicate that work-family conflict has a negative and significant impact on organizational commitment, while job satisfaction has a positive and significant impact on organizational commitment. Work-family conflict also has a negative and significant impact on nurse performance, while job satisfaction has a positive and significant impact on nurse performance. Furthermore, organizational commitment has a positive and significant impact on nurse performance. These findings suggest that work-family conflict and job satisfaction influence nurse performance and that organizational commitment mediates this relationship.